MICROSPHERULES OF NATIVE GOLD, SULFIDES, AND SULFOSALTS IN GOLD ORES - Novgorodova M.I.; Agakhanov A.A.; Dikaya T.V.; Gamyanin G.N.; Zhdanov Yu.Ya. (My University, 2004)
Mineral microspherules widespread in the gold-quartz ores of the Kellyam deposit, Yakutia, were analyzed on a microprobe; the morphology of their surface and the inner structures of microspherules composed of ore minerals were examined. Monomineralic (consisting of native gold, galena, antimonite, or pyrrhotite) and polymineralic zonal microspherules were distinguished, with the latter having gold cores and galenaboulangerite peripheral parts. The temperature interval of the origin of the microspherules was estimated at >850-200°C with the use of the method of invariant points. It is demonstrated that the values calculated for the sulfur and oxygen fugacities are attained in the gas phase in equilibrium with solids in the Au-Pb-Sb-S system saturated with hydrogen.